2020
DOI: 10.31234/osf.io/vtknh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rationalizing Constraints on the Capacity for Cognitive Control

Abstract: Humans are remarkably limited in (a) how many control-dependent tasks they can execute simultaneously, and (b) how intensely they can focus on a single task. These limitations are universal assumptions of most theories of cognition. Yet, a rationale for why humans are subject to these constraints remains elusive. This review draws on recent insights from psychology, neuroscience and machine learning, to suggest that constraints on cognitive control may result from a rational adaptation to fundamental computati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 100 publications
(153 reference statements)
10
59
0
Order By: Relevance
“…2 Note that neither EVC nor MIT provide a rationale for the resource conservation principle. Some have suggested that a cost of control results from computational dilemmas in neural systems (Musslick et al, 2017;Musslick, Jang, et al, 2018;Musslick & Cohen, 2020;Zénon et al, 2019) whereas others have suggested that such costs originate from biological constraints (e.g., Holroyd, 2016). A second crucial prediction made by MIT regards situations in which task difficulty remains unknown (unspecified) or where it can be determined by participants themselves (unfixed).…”
Section: Relationship To Mitmentioning
confidence: 99%
“…2 Note that neither EVC nor MIT provide a rationale for the resource conservation principle. Some have suggested that a cost of control results from computational dilemmas in neural systems (Musslick et al, 2017;Musslick, Jang, et al, 2018;Musslick & Cohen, 2020;Zénon et al, 2019) whereas others have suggested that such costs originate from biological constraints (e.g., Holroyd, 2016). A second crucial prediction made by MIT regards situations in which task difficulty remains unknown (unspecified) or where it can be determined by participants themselves (unfixed).…”
Section: Relationship To Mitmentioning
confidence: 99%
“…The neuronal congruency effects observed in the FEF support connectionist models such as the parallel distributed processing (PDP) model 12,58,59 , which suggest that the interference from task-irrelevant information occurred automatically and was induced by prior training 29,59 .…”
Section: Discussionmentioning
confidence: 59%
“…Yet, flexibility is a hallmark of cognition, with cognitive circuits shared across many different tasks (Fig. 3a) [64].…”
Section: Pre-training In Ecologically Relevant Environmentsmentioning
confidence: 99%